USE OF PERAMPANEL IN THE TREATMENT OF EPILEPSY: A REVIEW OF LITERATURE AND A CASE REPORT - K. Yu. Mukhin; O. A. Pylaeva (Русский журнал детской неврологии)
Despite a considerable advance made in epileptology, resistant epilepsies account for approximately 30 % of all forms of epilepsy particularly in patients with focal seizures. The most common structural cause of resistant epilepsies in children is focal cortical dysplasias that are varieties of abnormal cortical development. The term “focal cortical dysplasia” was first mentioned by D. Taylor et al. in 1971 to denote local abnormalities of cortical development in our 10 described patients with resistant epilepsy. According to К. Watanabe et al. (1996), focal cortical dysplasias as a cause of epilepsy are detected in 3.0–4.3 % of patients with different forms of epilepsy. Among all abnormalities of cortical development in children who have undergone surgery for epilepsy, focal cortical dysplasias amount to 75 %, as shown by the data obtained by I. Blümcke et al. (2009).In resistant epilepsy, there is a hope for successful neurosurgical treatment and synthesis of novel antiepileptic drugs (AEDs). The authors present a review dedicated to the novel AED perampanel and consider its mechanism of action, pharmacokinetic features, indications for use, and the results of clinical trials and postmarket researches of the efficacy, tolerability, and safety of the drug, including its recent investigations. The paper describes a clinical case of successfully using perampanel in a patient with therapy-resistant epilepsy caused by focal cortical dysplasia. Based on the data available in the literature and the authors’ own cases, it тay be concluded that perampanel is a promising drug in treating epilepsy (even in epilepsies resistant to many other AEDs) with favorable indicators of tolerability.